Relaksasi Otot Progresif dalam Manajemen Nyeri Pembedahan Ortopedi - Hendayani, Nurul; Masfuri, Masfuri (Journal of Telenursing (JOTING), 2024)
This writing aims to determine the effect of progressive muscle relaxation as a non-pharmacological therapy that can be used as a complementary or additional therapy in pain management in patients after orthopedic surgery. The method used was a systematic search for articles through the PubMed, Science Direct, Proquest, and Francis Taylor databases and published from 2013 to 2023 using the keywords "progressive muscle relaxation" AND "Pain" OR "Postoperative Pain" AND "Orthopedics surgery." From the search results, 11,262 articles were obtained, and it was determined that five articles that met the inclusion criteria were RCT (Randomized Control Trial) research studies. The study's results showed that 521 patients who met the inclusion criteria reported significant pain differences between the intervention and control groups. The intervention group given progressive muscle relaxation showed better pain reduction than the control group. The heterogeneity of study participants included patients after lumbar surgery (lumbar disc herniation, microdiscectomy, laminectomy), after TKA (Total Knee arthroplasty), and after tibiofibular fracture surgery. Four research articles provided progressive muscle relaxation interventions without combining them with other interventions, while one research article combined progressive muscle relaxation with other interventions in the form of physiotherapy. In conclusion, the latest evidence from several studies shows the role of progressive muscle relaxation as an additional or complementary therapy in managing pain in patients after orthopedic surgery, whether given together or without in combination with other interventions, shows positive results in helping reduce pain. Keywords: Pain, Orthopedic Surgery, Progressive Muscle Relaxation